2004
DOI: 10.1017/s095457940404444x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of theory of mind and executive functions to symptom type and severity in children with autism

Abstract: Although neurocognitive impairments in theory of mind and in executive functions have both been hypothesized to play a causal role in autism, there has been little research investigating the explanatory power of these impairments with regard to autistic symptomatology. The present study examined the degree to which individual differences in theory of mind and executive functions could explain variations in the severity of autism symptoms. Participants included 31 verbal, school-aged children with autism who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
4
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 84 publications
6
163
4
9
Order By: Relevance
“…Moreover, correlations between complement sentences and ToM also emerged despite this limitation, which suggests that EF abilities in ASD do not impact verbal ToM performance in the same way as specific complementation skills do. It is interesting to underline that recent studies that have found a relation between verbal theory of mind performance and executive control abilities in ASD have reported that associations between these components disappeared when the effects of non-verbal ability and language level on these variables were controlled (Joseph & Tager-Flusberg, 2004).…”
Section: Ef Tom and Complements: Interim Discussionmentioning
confidence: 98%
“…Moreover, correlations between complement sentences and ToM also emerged despite this limitation, which suggests that EF abilities in ASD do not impact verbal ToM performance in the same way as specific complementation skills do. It is interesting to underline that recent studies that have found a relation between verbal theory of mind performance and executive control abilities in ASD have reported that associations between these components disappeared when the effects of non-verbal ability and language level on these variables were controlled (Joseph & Tager-Flusberg, 2004).…”
Section: Ef Tom and Complements: Interim Discussionmentioning
confidence: 98%
“…For example, when an individual participates in a group discussion, s/he must track multiple speakers' comments simultaneously, while generating and modifying his/her own contributions. Moreover, there is also a large literature, which will not be reviewed here, connecting 'theory of mind' deficits and EF (see Carlson, Moses, & Claxton, 2004;Hughes, 2001;Joseph & Tager-Flusberg, 2004 for recent developments in this area of research). Systematic research must be conducted to clarify the contribution of social experience throughout development on cognitive and neural mechanisms underlying EF, and how deviation from typical social experiences contributes to an emergent deficit as seen in autism.…”
Section: Discussionmentioning
confidence: 99%
“…verbal tasks and tasks requiring inference of the experimenter's intentions) or because these two cognitive processes fundamentally rely on a common cognitive mechanism. Despite a lack of clarity as to the roots of this association, the past literature in ASD certainly supports the existence of such a relationship (Joseph & Tager-Flusberg, 2004;Ozonoff, Pennington, & Rogers, 1991;Zelazo, 2002). …”
Section: Cognitive Fractionationmentioning
confidence: 99%